Peningkatan Kemampuan Numerasi Menggunakan Model Problem Based Learning Berbantu Media Puzzle Penjumlahan Kelas I SDN Tlogosari Kulon 01 Semarang - Kusumaningrum, Aderisca; Subekti, Ervina Eka; Setyawati, Rina Dwi; Wati, Lisa (Jurnal Penelitian Multidisiplin Ilmu, 2024)
This study aims to analyze the increase in the average score of the pretest and posttest numeracy scores in numeracy literacy activities in class I SDN Tlogosari Kulon 01 Semarang before and after using the addition puzzle media. The research design used a quantitative experiment, namely Pre-Experimental Design with the One-Group Pretest-Posttest Design model. Data obtained through written test method. The location of this research will be implemented in class I SDN Tlogosari Kulon 01 Semarang. The sample in this study were 30 grade I students using saturated sampling technique. The results showed that the results of the N-Gain test using SPSS 23, obtained an average of 0.46 which means an increase with moderate criteria. So, it can be concluded that the application of the addition puzzle media provides an increase in the pretest and posttest scores of students before and after using the addition puzzle media on the numeracy skills of grade I students of SDN Tlogosari Kulon 01 Semarang.